Development of a telerobotic test bench system for small-field-of-operation bilateral applications with 3D visual and haptic (kinaesthetic) feedback - Smit, Andre (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScEng) Stellenbosch University, 2014